Celebrating the 60th anniversary of the Asia Pacific Journal of Human Resources: what has been achieved and what more can be done. (3rd December 2021) - Bartram, Timothy; Cooke, Fang Lee
Abstract : The Asia Pacific Journal of Human Resources ( APJHR ) celebrates its 60 th anniversary in 2022. In this 60 th anniversary issue, we provide a brief overview of the APJHR and its recent developments. We outline a few thematic areas, with indicative research questions that would facilitate researchers to extend the field of HRM research with policy relevance and societal impact in the Asia Pacific, drawing on several megatrends as the context. These include demographic changes, climate change and energy transition, digital technology and the growing interest in HR analytics, and the global pandemic. We then present a collection of review articles included in this anniversary issue that provide a critical appraisal, from a historical lens, of selected research topics including those published in the APJHR ; we reflect on how they have evolved and what further research efforts can be exerted to advance the field.